Development and Application of Bovine and Porcine Oligonucleotide Arrays with Protein-Based Annotation. (14th December 2010) - Garbe, John R.; Elsik, Christine G.; Antoniou, Eric; Reecy, James M.; Clark, Karl J.; Venkatraman, Anand; Kim, Jae-Woo; Schnabel, Robert D.; Michael Dickens, C.; Wolfinger, Russell D.; Fahrenkrug, Scott C.; Taylor, Jeremy F.
Abstract : The design of oligonucleotide sequences for the detection of gene expression in species with disparate volumes of genome and EST sequence information has been broadly studied. However, a congruous strategy has yet to emerge to allow the design of sensitive and specific gene expression detection probes. This study explores the use of a phylogenomic approach to align transcribed sequences to vertebrate protein sequences for the detection of gene families to design genomewide 70-mer oligonucleotide probe sequences for bovine and porcine. The bovine array contains 23, 580 probes that target the transcripts of 16, 341 genes, about 72% of the total number of bovine genes. The porcine array contains 19, 980 probes targeting 15, 204 genes, about 76% of the genes in the Ensembl annotation of the pig genome. An initial experiment using the bovine array demonstrates the specificity and sensitivity of the array.